Family Members' Experience of Discussions on End-of-Life Care in Nursing Homes in Japan: A Qualitative Descriptive Study of Family Members' Narratives - Kato, Hiroki (J Hosp Palliat Nurs, 2020)
In nursing homes, discussions between family members and staff regarding the end of life for residents with cognitive impairment are crucial to the choice of treatment and care consistent with residents' wishes. However, family members experience burden in such discussions, and communication with staff remains inadequate. The purpose of this qualitative descriptive study was to elucidate the meaning of continuous end-of-life discussion for family members. Data were collected using semistructured individual interviews. Thirteen family members of residents from 3 nursing homes in Kyoto, Japan, participated in the study. Data were analyzed using thematic analysis, which focused on both explicit and implicit meanings. Four themes emerged regarding the experience of end-of-life discussion: “the end of life soaking in,” “hardship of making the decision to end my family member's life,” “wavering thoughts about decisions made and actions taken,” and “feeling a sense of participation about the care.” Family members had come to accept the deaths of residents through continuous discussion and experienced strong conflict in facing the death of their family members. Moreover, staff members should understand family members' beliefs and the burden they experience in facing residents' death.